Entwicklung der Einzelhandelszentralität Zentraler Orte in Mittelhessen 1967-1986 - Giese, Ernst (ERDKUNDE, 1991)
In 1968, the Regional Planning Commission of the F.R.G. (Ministerkonferenz für Raumordnung) decided to use the central place theory as a major theoretical concept for regional planning policies. Since then, central places have become the focus of regional plans at various planning levels (LandesentwicklungsPläne and Regionale RaumordnungsPläne). In Hesse, the central place concept was introduced in 1970 (so-called Großer HessenPlan). After 20 years of planning practise the question is raised as to whether the central place hierarchy has changed. Is it still possible to update central place hierarchies to actual developments or is it necessary to reorganise the central place system completely? Using the planning region of Central Hesse, changes in the central place hierarchy are analysed and causes identified accordingly. The relation between centrality and nodality of central places in particular is investigated. Because of insufficient data the analysis is limited to retail data.